2008
DOI: 10.1007/s00269-008-0261-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity of natural and synthetic garnet solid solution series

Abstract: Knowledge of heat transport properties as a function of mineral-and rock-composition and temperature is of major relevance to understand and model heat transfer in the Earth's interior. A systematic study on 13 natural and 4 synthetic garnets was carried out in an attempt to obtain a better systematic understanding of the processes that affect the heat transport in minerals, especially the effect of chemical substitution in solid solution series. It is found that substitution significantly lowers the thermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…Figure 5 shows thermal diffusivity as a function of the concentration (X) of SNAB + XNd 2 O 3 (wt.%). The decrease of D as Nd 3+ concentrations increase may be attributed to additional variations of local density due to different atoms and vacancies, especially oxygen, which is known to efficiently scatter elements [25,[28][29][30]. Similar results were observed in Yb 3+ doped laser crystals [25].…”
Section: Discussionsupporting
confidence: 85%
“…Figure 5 shows thermal diffusivity as a function of the concentration (X) of SNAB + XNd 2 O 3 (wt.%). The decrease of D as Nd 3+ concentrations increase may be attributed to additional variations of local density due to different atoms and vacancies, especially oxygen, which is known to efficiently scatter elements [25,[28][29][30]. Similar results were observed in Yb 3+ doped laser crystals [25].…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the predicted pressure dependence of thermal diffusivity of Hofmeister (2007). Furthermore, a recent study (Marquardt et al, 2009) surveyed the thermal diffusivities of a wide range of natural and synthetic garnets at atmospheric pressure and concluded that, in the high-temperature limit, they all had the same value of thermal diffusivity, D min , of 6.4(3) x 10 -7 m 2 /s. This compares very well with the present high-temperature limit value of 6.2(5) x 10 -7 m 2 /s and gives us confidence that the present results for MORB composition majorite at 15 GPa are robust.…”
Section: Comparison With Previous Resultssupporting
confidence: 74%
“…The influence of temperature and dopants on phonon velocities, both longitudinal and transverse, can be neglected [7,[13][14][15]. Thus, changes in the thermal diffusivity, caused by these factors, are almost completely defined by the changes in the mean free path of phonons.…”
Section: Introductionmentioning
confidence: 98%